Development of household solid waste sorting in Nasor village, Wanonniwad District, Sakonnakorn Province - ณ นครพนม ศิรินุช; อินทร์ม่วง อุไรวรรณ (Disease Control Journal, 2014)
The purposes of this study were 1) to study and compare the knowledge and attitude of waste disposal management and to study and compare the amount of household waste before and after the intervention. This study was conducted in Nasor sub-district, Wanonniwad district, SakonNakhon province during December 2012 to September 2013. Data were collected from 128 households using questionnaire regarding waste management and knowledge and attitude of waste management as well. The meeting was organized to develop intervention focused on three activities including cleaning house, Phapa Ceremony, and food ingredient market. Data were analyzed using descriptive statistics including percentage, mean and standard deviation. The comparison between the knowledge and attitude of waste management before and after intervention was analyzed using Paired-t-test. The results of this study showed that after the intervention the amount of household waste per day was reduced significantly 31.70% (P-value < 0.001). In addition, the average of the knowledge and attitude of waste disposal management after intervention were significantly higher than of those before intervention (P-value < 0.001). In conclusion, the household waste disposal management intervention which participated by local people and community’s leader could increase awareness of people and finally the household waste in community has been reduced.